How Does the FDA Evaluate AI Software as a Medical Device? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) and machine learning (ML) are no longer concepts confined to science fiction; they are rapidly becoming integral components of m...
Keywords: FDA Regulation and Compliance; Evaluate; Software; Medical; Artificial Intelligence; Machine Learning; Healthcare